2017
DOI: 10.1111/chd.12558
|View full text |Cite
|
Sign up to set email alerts
|

A composite noninvasive index correlates with liver fibrosis scores in post-Fontan patients: Preliminary findings

Abstract: Objective: We hypothesized that clinic-based, hepatic-ultrasound, elastography measurements, either alone or in combination with other noninvasive variables, might correlate with liver-biopsy fibrosis scores in patients post-Fontan. Results: We identified a total of 79 post-Fontan patients that underwent cardiac catheterization and liver biopsy. Of the 79 patients, 53 met inclusion criteria, and 32 consented to undergo hepatic-ultrasound elastography. Of the 32 that underwent elastography, data from 30 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…We also found that, similarly, ultrasound, shear-wave elastography scores were higher in those with venovenous collaterals vs those without col- past studies failed to show a statistically significant effect from a range of inferior vena caval pressures on either TFS or FPR. 17,20 Additional strengths include our robust data management and electronic health records on all diagnosed patients in Nevada, avoiding the reliance on third-party sources such as hospital discharge information or state databases. Finally, data were culled from a relatively young, stable population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that, similarly, ultrasound, shear-wave elastography scores were higher in those with venovenous collaterals vs those without col- past studies failed to show a statistically significant effect from a range of inferior vena caval pressures on either TFS or FPR. 17,20 Additional strengths include our robust data management and electronic health records on all diagnosed patients in Nevada, avoiding the reliance on third-party sources such as hospital discharge information or state databases. Finally, data were culled from a relatively young, stable population.…”
Section: Discussionmentioning
confidence: 99%
“…16 We previously demonstrated the better correlating strength for the TFS than individual portal or sinusoidal fibrosis scores, when compared with variables such as laboratory values, hemodynamic measurements, and elastography scores. 17 For each patient, we calculated a value for the hepatic fibrosis EVANS ET AL.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic accuracy of the FibroScan system for hepatic fibrosis has been validated in chronic viral hepatitis and nonalcoholic fatty liver disease. However, evidence of the utility of ultrasound-based elastography for cardiac hepatopathy remains insufficient [23,93,[103][104][105][131][132][133][134][135][136][137][138][139][140]. Because ultrasound-based elastography cannot differentiate blood from fibrosis, congestion influences the liver stiffness assessed by elastography.…”
Section: Elastographymentioning
confidence: 99%
“…At this time, Evans and colleagues studied a noninvasive composite Fontan hepatic index in 30 adult Fontan patients who underwent cardiac catheterization and liver biopsy. 60 They found that a composite index composed of hepatic ultrasound elastography measurements, MELD scores (Model for End Stage Liver Disease), and time post-Fontan strongly correlated with the total fibrosis score from liver biopsy.…”
Section: Adult Congenital Heart Diseasementioning
confidence: 98%